Change of stress-deformed mode of the slope masses during developing and operation of excavations in it - Vynnykov, Yuriy; Kharchenko, Maksym; Yaholnyk, Andrii; Lystopad, Serhii (Academic journal Industrial Machine Building Civil Engineering, 2020)
Peculiarities of structure geomorphological and engineering-geological features on the site with artificial excavation in the water basin form, the surface water valley runoff into the reservoir, and the soils properties are determined. Negative engineering-geological processes on the site and the reasons for the activation of landslide processes are considered. A slope spatial model is compiled. The slope stability was assessed taking into account the peculiarities of geological and hydrogeological structure using the structural soil strength. Sliding planes and shear pressures on possible landslide protection structures are determined. A "reverse" calculation of the slope stability was also performed to clarify the characteristics of soil strength. It is established that when arranging excavations in the slope array, its SDM changes, which activates landslides.
Keywords: slope; artificial excavation; landslide; comb; soil strength; cohesion; stress-deformed mode; finite element method; ultimate equilibrium method; one plane shear testing; «plate-by-plate» method